Pengembangan Aplikasi Inventaris Berbasis Website Menggunakan Metode Rapid Application Development - Willi Novrian; Yeyi Gusla Nengsih; Darmansah Darmansah (Journal of Information System Research (JOSH), 2022)
Information technology has become an important requirement in advancing the company. Various information technologies that can be used for work purposes, one of which is a website-based application. At the General Finance Education and Training Center, there are still deficiencies in loan management in the areas of administration with households and asset management. The management of borrowing goods that occur is not well coordinated so that they experience a lack of effectiveness and efficiency in working as needed by the world of work in the current era. So to overcome these problems, the researchers designed an application for borrowing and returning goods based on a website. In this study, the method used is RAD (Rapid Application Development) then in software modeling the researcher uses UML modeling. The result of this research is to create an inventory website that can help in managing goods at the Financial Education and Training Center.